Pengaruh Kepuasan dan Motivasi Kerja terhadap Komitmen Afektif Guru SMK Negeri Di Jakarta Selatan - Ahmad Zainul Mizan; Rugaiyah Rugaiyah; Nurjanah Nurjanah (Universitas Indraprasta PGRI Jakarta, 2018)
The researcher’s observation of the condition of SMKN (State Vocational High School) teachers in South Jakarta and interview with the deputy headmaster overseeing curriculum and student affairs show a gap between the expectation and the reality of the teacher's affective commitment. Based on empirical data obtained from preliminary interviews in March 2018 in several SMKNs in South Jakarta, it is seen that the teacher’s affective commitment to teach is still low. This research aims to know the effects of (1) Job Satisfaction, (2) Work Motivation, (3) Affective Commitment of SMKN teachers in South Jakarta. The method used is a survey research method with a quantitative-causal approach using path analysis. The survey is conducted from June to July 2018 by involving samples of 164 teachers randomly taken in South Jakarta. The findings in the research show: First, there is a direct effect of job satisfaction on affective commitment. Second, there is a direct effect of work motivation on affective commitment. Third, there is a direct effect of job satisfaction on work motivation.